O ENSINO DE FÍSICA NO SISTEMA PRISIONAL - Souza, Jucimara Felix dos Santos de (2019)
According to literature one of the ways to reduce the distance between the theory exposed in the classroom and the physical phenomena of students' everyday life is the use of experimental classes to demonstrate and study such phenomena. However, there are some difficulties for the application of these classes due to the absence of science labs in some schools, including the school inside the prison system, since it is prohibited the entrance of any pointed material, the use of fire, electrical wires , glass or any other material that may pose a risk to the safety of the system. The work proposes the use of technology - videos with experiments - as an auxiliary tool to the lectures and had as a theoretical reference the theory of Significant Learning of David Ausubel, considering the previous knowledge of the student. The evidence of conceptual evolution after the use of this tool was analyzed through two questionnaires, one open and one closed, identifying previous knowledge and the way students use the terms heat and temperature and their definitions. After the analysis of these questionnaires, a didactic sequence on temperature and heat was prepared containing experiments with daily scenes in videos about the propagation of heat, which were transmitted through television, which the students of the prison system have access to. A total of 25 students, from the second stage of high school - EJA, were submitted to the tests and after the didactic sequence was administered, the questionnaire was applied to verify the students' learning, being necessary a total of 6 classes, lasting 50 minutes. The results showed that there were improvements in the understanding of the initial Physical concepts of Thermodynamics, and consequently, a scientific literacy. The motivation to understand the physical phenomena of daily life may have been fundamental to achieve these results. The use of television in physics teaching has awakened a didactic look at other teachers, becoming a usual tool in other disciplines for teaching classes with documentaries, slides and even videos. It is noteworthy that during the literature review on the teaching of sciences in the prison system, researches were only found in the fields of Chemistry and Biology, making the present research as a pioneer in the teaching of Physics in the prison system.